2006
DOI: 10.1007/s00270-005-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contrast-Enhanced Ultrasound and Computed Tomography in Classifying Endoleaks After Endovascular Treatment of Abdominal Aorta Aneurysms: Preliminary Experience

Abstract: The purpose of the study was to assess the effectiveness of contrast-enhanced ultrasonography (CEUS) in endoleak classification after endovascular treatment of an abdominal aortic aneurysm compared to computed tomography angiography (CTA). From May 2001 to April 2003, 10 patients with endoleaks already detected by CTA underwent CEUS with Sonovue to confirm the CTA classification or to reclassify the endoleak. In three conflicting cases, the patients were also studied with conventional angiography. CEUS confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
28
0
5
Order By: Relevance
“…The emergent role of CEUS and its growing indications compared to CT are also shown by several studies in different fields [24][25][26][27], which prove its applications in the body, for liver, kidney, testis, lymph nodes, thyroid, prostate and small bowel. CEUS with low-mechanical index technique, evaluated in some studies for the EVAR follow-up [8,9,28,29], used second-generation ultrasound contrast agents (e.g., SonoVue Ò ) which employ gas microbubbles of sulfur hexafluoride encapsulated by phospholipid shells. They circulate with a good concentration up to 10 min offering, with harmonic imaging, pure vascular enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergent role of CEUS and its growing indications compared to CT are also shown by several studies in different fields [24][25][26][27], which prove its applications in the body, for liver, kidney, testis, lymph nodes, thyroid, prostate and small bowel. CEUS with low-mechanical index technique, evaluated in some studies for the EVAR follow-up [8,9,28,29], used second-generation ultrasound contrast agents (e.g., SonoVue Ò ) which employ gas microbubbles of sulfur hexafluoride encapsulated by phospholipid shells. They circulate with a good concentration up to 10 min offering, with harmonic imaging, pure vascular enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, some valid alternatives to CT are contrast-enhanced ultrasound (CEUS) and magnetic resonance angiography (MRA) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Several different studies have therefore been conducted to compare the precision of vascular ultrasonography with that of angiotomography for classification of endoleaks. [12][13][14] The objective of this study was to determine the correlation, sensitivity and specificity of the ultrasonography method, with relation to angiotomography, for measurement of aneurysm diameter, identification of tortuosity and for detection and classification of endoleaks.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is considered to be more accurate than ultrasound without contrast, and similar to magnetic resonance imaging (MR) and CT (Cantisani et al, 2011;Iezzi et al, 2009;Mirza et al, 2010;Sun 2006). McWilliams et al (2002) investigated 53 patients and found contrast enhanced ultrasound to be more sensitive than unenhanced ultrasound in detection of endoleak when compared to CT, but concluded that ultrasound (with or without contrast) was less reliable than CT. On the contrary, several other authors have concluded that contrast enhanced ultrasound may perform better than CT in detection of endoleak (Carrafiello et al, 2006;Clevert et al, 2008;Henao et al, 2006;Ten Bosch et al, 2010). Bakken & Illig (2010) presented a review summarizing use of ultrasound for detection of endoleak.…”
Section: Ultrasound In Post-operative Surveillancementioning
confidence: 99%